Capital Convertible In Huripjaya Village, Babelan District, North Bekasi Regency - Wimba Wisesa; Robert M.Z Lawang (Al-Makki Publisher, 2023)
This study examines capital convertibility in Huripjaya Village, Babelan District, North Bekasi Regency. Capital convertibility refers to the ability of capital or economic resources to switch between forms or sectors to improve people's welfare. The main objective of this study is to analyze the dynamics of capital convertibility, the factors that influence it, and its impact on village development. The research method used is a combination of literature studies, field observations, and interviews with key stakeholders in Huripjaya Village. The results showed that the convertibility of capital in this village was influenced by internal and external factors, including geographical conditions, natural resources, institutions, and regional economic development. Factors such as economic diversification, the role of microfinance institutions, and community involvement in local decision-making play an important role in increasing capital convertibility. In addition, the existence of community economic training and education programs was also identified as a factor that contributed positively to economic structural changes in Huripjaya Village. In the context of development impacts, this study presents findings that increasing capital convertibility can make a significant contribution to improving the welfare of rural communities. This can be seen from the increase in population access to better health services, education, and infrastructure. This research provides valuable insights for policy makers, local governments, and other relevant parties to design more effective and sustainable development strategies at the village level.